Urinary iodine excretion in urine samples among children in Dang district, Gujarat - Damor, Rahul; Chhaya, Jatin; Gamit, Sukesha; Patel, Jayant; Kosambiya, J. K. (International Journal Of Community Medicine And Public Health, 2017)
Background: Iodine is an essential micronutrient required for normal human growth and development as it is needed for the synthesis of thyroid hormones produced by thyroid glands. The sicknesses occurred due to deficiencies of iodine in the nutrition are termed iodine deficiency disorders. Urinary iodine concentration is the prime indicator of a person’s nutritional iodine status. So, the aim of this study was to assess the status of iodine deficiency based on median urinary iodine excretion. Methods: Community based cross sectional study was carried out among purposively selected primary schools of the Dang district. All students between the age group of 6 to 12 years who were present on the day of visit were included in the study. A total 387 urine samples were collected during the period of August 2015 to September 2016. Results: Based on median urinary iodine excretion, among total analysed samples, about 6.5% samples confirmed severe iodine deficiency, 22% samples showed moderate iodine deficiency and about 36% samples indicated mild iodine deficiency. About one third (31.3%) samples suggested optimum iodine intake. Only few samples (4.4%) revealed more than required iodine intake. Conclusions: About one third (31.3%) of the surveyed population had adequate iodine intake while majority (64.4%) of them had inadequate iodine intake.